Evaluation of oxidative status in patients with hyperthyroidism - SELEK, ŞAHABETTİN; Aslan, Mehmet; Cosar, Niyet; Celik, Hakim; Aksoy, Nurten; Dulger, Ahmet Cumhur; Begenik, Huseyin; Soyoral, Yasemin Usul; Kucukoglu, Mehmet Emin; Selek, Sahbettin (My University, 2011)
Data on the antioxidant levels enzyme in patients with hyperthyroidism are limited and conflicting. Therefore, the objective of this study was to evaluate the oxidative status using an automated method in patients with hyperthyroidism. Thirty-six subjects with hyperthyroidism and 30 healthy controls were enrolled in this study. Serum oxidative status was determined via measurement of total antioxidant capacity (TAC) and total oxidant status (TOS) and calculation of oxidative stress index (OSI). Serum TAC levels were significantly lower in patients with hyperthyroidism than controls (P = 0.002), while serum TOS levels and OSI values were significantly higher (P = 0.008, 0.004; respectively). Serum TAC levels were correlated with TSH levels (rho = 0.223, P = 0.032), FT3 levels (rho = -0.434, P = 0.002) and FT4 levels (rho = -0.363, P = 0.003) in patients. Further, TOS levels and OSI values were correlated with TSH levels (rho = -0.245, P = 0.037; rho = -0.312, P = 0.011, respectively), FT3 levels (rho = 0.293, P = 0.017, rho = 0.505, P = 0.002, respectively), and FT4 levels (rho = 0.302, P = 0.006, rho = 0.321, P = 0.008, respectively) in patients. Duration of disease was significantly correlated with OSI values in patients (rho = 0.420, P = 0.011), while no correlation with serum TAC levels and TOS levels (P > 0.05). Oxidants are increased and antioxidants are decreased in patients with hyperthyroidism; as a result, the oxidative-antioxidative balance is shifted to the oxidative side. Increased oxidative stress may play a role in the pathogenesis of hyperthyroidism. It is believed that supplementation of antioxidant vitamins such as vitamins C and E may be helpful for these patients.